PENGARUH KOMPETENSI PEGAWAI DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA DI BALAI KALIBRASI FASILITAS PENERBANGAN - Samsu Rohmat (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
As an organization tasked with carrying out aviation calibration aviation activities, the Aviation Facility Calibration Center must be able to provide calibration services to all airports in Indonesia with high quality and on time as scheduled. To carry out these tasks, the Aviation Facility Calibration Center urgently needs the support of quality resources. To prove this effort, this research was carried out as a study to review the productivity of flight calibration staff. The object of this study is the staff ofthe Flight Calibration Facility Center Ministry of Transportation. According to the Slovin Formula, taking sample was done by the procedure of proportionate stratified random sampling. The sample was taken by fifty participants. The findings show that productivity is very dependent on competence. while motivation becomes the dominant condition variable for work attitudes and behavior. Keywords: Competence, Motivation, Productivity